Pendampingan Audit Eksternal Halal Oleh Lembaga Pemeriksan Halal dan Kajian Halalan Thayyiban (LPHKHT) Muhammadiyah Di Usaha Mikro Kecil dan Menengah (UMKM) Today Bakery Sidoarjo, Jawa Timur - Wahyuni, Hana Catur; Nur Ravita Hanus; Dina Okta; Hasan Ubaidillah; Halim, Muhammad; Aulia Putri S (Jurnal Pengabdian Multidisiplin, 2024)
This community service activity aims to assist Today Bakery MSMEs to carry out halal external audits in order to apply for halal certification. The implementation method is carried out in three stages, namely preparation which is carried out starting H-2 from the schedule received, implementation is carried out according to schedule and evaluation is carried out H+3 from implementation. Community service activities resulted in the submission of halal certification by Today Bakery through LPHKHT Muhammadiyah. The external audit by LPHKHT Muhammadiyah auditors was carried out on 18 December 2023 by sending 2 auditors. The audit agenda was carried out with an opening attended by all elements of Today Bakery, document verification and field visits and ended with closing. In the closing, the results of the audit and recommendations for improvement were explained and the minutes of the audit were signed by the Today Bakery leadership and the LPHKHT Muhammadiyah auditors.